Epidural Hematoma After Thoracic Epidural Catheter Removal in the Absence of Risk Factors. Issue 6 (1st November 2003) - Sidiropoulou, Tatiana; Pompeo, Eugenio; Bozzao, Alessandro; Lunardi, Pierpaolo; Dauri, Mario
Abstract : Background and Objectives: The purpose of this report is to enhance awareness that an epidural hematoma can occur even in patients devoid of risk factors. Case Report: A 69-year-old, 55-kg male was scheduled for video-assisted thoracoscopic resection of bilateral pulmonary metastases and received combined thoracic epidural and general anesthesia. The epidural catheter insertion was unremarkable. All laboratory values were within normal values. No anticoagulation or antiplatelet drugs were administered. The epidural catheter was removed on postoperative day 2. The patient developed signs of an epidural hematoma a few hours later and was treated by decompressive laminectomy. Full neurologic recovery was observed after a 6-month period. Conclusion: Catheter removal is a critical period for epidural hematoma formation even if no risk factors are identified. Early recognition and treatment are essential features for good neurologic recovery after an epidural hematoma.